Agricultural Drought Monitoring System Country-level ASIS Launching Workshop - Ahmed, Jemal Seid; Grossi, Amanda; Dinku, Tufa; Makonnen, Brook T. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
On January 20, 2022, the Ethiopian Institute of Agricultural Research (EIAR), the Ethiopian Meteorological Institute (EMI), and the International Research Institute for Climate and Society (IRI) with the collaboration of the CGIAR Research Program on Climate, Change Agriculture, and Food Security (CCAFS) launched an agricultural drought monitoring and warning platform in Ethiopia. During the launching workshop, over 100 key stakeholders including researchers, academics, policymakers, development practitioners, media, and officials from the public and private sectors participated.